PENERAPAN DATA MINING PADA PENJUALAN TAN’S BAKERY MENGGUNAKAN ALGORITMA APRIORI - Desak Made Dwi Utami Putra; Setio Budiono (LPPM Universitas Dhyana Pura, 2017)
ABSTRACT PT.Tan's Bakery is a manufacture company of food that provides a variety of bread products(Bakery) and cakes (Pastry) to supply the needs of Hotels, Villas, and Restaurants in Bali inparticular. There are a lot of products that are produced and offered to its customers ranging fromEuropean bakery products to international-standard pastry products, frequent daily activities atPT.Tan's Bakery among others, order receipt, product manufacturing instructions, product stockprovision, procurement raw materials, customer additions, etc. In this study developed datamining analysis system using a priori algorithm is expected to give solution because by applyingdata analysis using a priori algorithm at Tan's Bakery can generate useful information forcompany, in analyzing sales transaction besides saving time, high, from the results of testingconducted obtained the results of the developed system is running as expected. Keywords: Tan's Bakery, Apriori, Data Mining, Support & Confident. ABSTRAK PT.Tan’s Bakery merupakan suatu perusahaan yang bergerak dalam bidang pembuatanmakanan yang menyediakan berbagai produk roti (Bakery) dan kue (Pastry) untuk menyuplai kebutuhan Hotel, Villa, dan Restoran yang ada di Bali khususnya. Ada banyak sekali produkprodukyangdiproduksidanditawarkankepelanggannyamulaidariprodukbakeryEropahinggaprodukpastry yang bertaraf International, kegiatan yang sering dilakukan setiap hari padaPT.Tan’s Bakery diantara lain, penerimaan pesanan, intruksi pembuatan produk, penyediaan stokproduk, pengadaan bahan baku, penambahan pelanggan,dll.Pada penelittian ini dikembangkansistem analisis data mining menggunkan algoritma apriori diharapkan dapat memeberikan solusikarena dengan menerapkan analisis data nining menggunkan algoritma apriori pada Tan’s Bakerydapat menghasilkan informasi yang berguna bagi perusahaan, dalam menganalisis transaksipenjualan selain menghemat waktu, tingkat keakuratan informasi yang dihasilkan menjadi lebihtinggi, dari hasil pengujian yang dilakukan didapat hasil sistem yang dikembangkan sudah berjalan sesuai dengan yang diharapkan. Kata Kunci: Tan’s Bakery, Apriori, Data Mining, Support & Confident.